Use of Complementary and Alternative Medicine Practices in Patients Admitted to The Pediatric Neurology Outpatient Clinic - Deniz Yüksel; Ergin Atasoy; Ülkühan Öztoprak; Erhan Aksoy; Fatih Mehmet Akif Özdemir; Halil Celik; Nesrin Ceylan (Genel Tıp Dergisi)
Introduction: Despite the developments in pharmacologic treatments, traditional and complementary therapies have recently gained popularity in our country, as well as around the world. Aim: To question complementary and alternative medicine practices CAMP during clinical visits of pediatric neurology patients, to raise awareness of families and patients about the use of complementary and alternative medicine, and to prevent possible negative interactions. Methods: This prospective survey study was conducted with the parents of 300 pediatric patients aged between 6 months and 18 years, who were being treated at the Child Neurology Clinic between March 1st and May 30th, 2020. For the study, 360 patients’ parents who came to the Pediatric Neurology clinic for treatment were randomly selected, and a face-to-face survey lasting 2 minutes was conducted with 300 patients’ parents who agreed to participate in the study. This study was approved with the decision number E-20-12-62 at the meeting dated 21.12.2020 of the Clinical Research Ethics Committee of SBU Ankara Dr Sami Ulus Gynecology and Childhood Health and Diseases Training and Research Hospital. Results: Three hundred parents (56% women) participated in the study. Just over half (55.3%) of the patients were followed up with a diagnosis of epilepsy, 56.6% of the parents stated that they had used traditional and complementary therapy methods before, 43.4% stated that they did not use it, 46.54% stated that they used prayer and 23,9% used vitamin methods, respectively. Conclusion: In neurologic diseases, parents use traditional and complementary therapies as treatment methods, creating an alternative to modern medicine. Families and patients should be informed by investigating the reasons and frequency of using traditional and complementary therapies, raising the awareness of parents, and determining the possible harm caused by traditional and complementary therapies.